In vitro and Quantitative and Structure Activity Relationship (QSAR) evaluation of the antifungal activity of terpenoid constituents of essential oils against Alternaria alternata and Fusarium oxysporum. - Andrade-Ochoa, Sergio; Sánchez-Aldana, Daniela; María Rodríguez-Valdez, Luz; Virginia Nevárez-Moorillón, Guadalupe (Biomédica: Revista del Instituto Nacional de Salud)
Introduction. Fungal genera Alternaria and Fusarium include human and plant pathogenic species. Several antifungals have been used for their control, but excessive use has contributed to resistance development in pathogens. An alternative to searching for and developing new antifungal agents is using essential oils and their main components, which have biological activities of interest in medicine and food production. Objective. To evaluate in vitro and in silico the antifungal activities of terpenoids against Alternaria alternata and Fusarium oxysporum. Materials and methods. The minimum inhibitory concentration and minimum fungicidal concentration values of 27 constituents of essential oils used against Alternaria alternata and Fusarium oxysporum were evaluated in vitro. In addition, using genetic algorithms, quantitative models of the structure-activity relationship were used to identify the structural and physicochemical properties related to antifungal activity. Results. The evaluated compounds proved to be effective antifungals. Thymol was the most active with a minimum inhibitory concentration of 91.6 ± 28.8 µg/ml for A. alternata and F. oxysporum. Quantitative structure-activity relationship models revealed the octanolwater cleavage ratio as the molecular property, and the phenols as the main functional group contributing to antifungal activity. Conclusion. Terpenoids exhibit relevant antifungal activities that should be incorporated into the study of medicinal chemistry. Inclusion of in silico assays in the in vitro evaluation is a valuable tool in the search for and rational design of terpene derivatives as new potential antifungal agents.